Bio-based anti-ultraviolet finishing agent and preparation method thereof

By sorting the nano core-shell composite cellulose-based anti-UV finishing agent on the fabric, the problems of low affinity and poor dispersion stability of the UV absorber with polymer substrates are solved, and the sun resistance and strong maintenance of the fabric are significantly improved. performance.

CN119287655APending Publication Date: 2025-01-10JIANGSU NEW REBA TECH CO LTD +1

Patent Information

Application Number
CN202411418866.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the prior art, the ultraviolet absorber has a low affinity with the polymer substrate and poor dispersion stability, resulting in insufficient sun resistance and strong retention properties of the fabric during long-term exposure to ultraviolet rays.

Method used

Using bio-based anti-ultraviolet finishing agent, nanocore-shell composite cellulose-based anti-ultraviolet finishing agent is formed by ultrasonic dispersing the ultrasonic agent and shielding agent with cellulose nanofibers and stirring at specific temperatures and stirring conditions. Using the spontaneous drying film-forming properties of cellulose nanofibers, it is simply organized on the surface of the fabric and encapsulates the ultraviolet absorber.

Benefits of technology

It significantly improves the sun resistance and strong retention properties of the fabric under high-strength ultraviolet radiation, avoids the use of additional chemical crosslinking and polymer film forming materials, and achieves effective protection of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005080203760000061
    Figure BDA0005080203760000061
  • Figure BDA0005080203760000071
    Figure BDA0005080203760000071
Patent Text Reader

Abstract

The invention discloses a preparation method of a bio-based anti-ultraviolet finishing agent, which comprises the following steps: (1) adding an ultraviolet light absorber and / or an ultraviolet screening agent into a solvent, and carrying out ultrasonic dispersion to prepare a dispersion liquid; and (2) adding cellulose nanofibers into the dispersion liquid, and stirring at 30-70 DEG C for 2-6 hours to obtain the biotin-based anti-ultraviolet finishing agent, the length-diameter ratio of the cellulose nanofiber is 100 to 10000. According to the invention, dye chromophoric groups and macromolecular chain segments on the fabric are effectively protected through a simple coating finishing process, and the solarization resistance and the strength retention performance of the fabric under outdoor high-strength ultraviolet irradiation are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fine chemicals, and in particular to a bio-based anti-ultraviolet finishing agent and a preparation method thereof. Background Art

[0002] With the rapid development of the outdoor textile industry, the serious fading and strength loss of outdoor tents, parasols, awnings and other fabrics that have been exposed to ultraviolet light for a long time have attracted widespread attention. So far, the results of studies on improving the sun resistance and strength retention of fabrics by directly applying various types of functional ultraviolet absorbing additives have shown that the ultraviolet absorbers on the surface of fabrics can strongly absorb ultraviolet rays before the dye chromophores and polymer segments, and by cutting off the energy source of photochemical reactions, change or delay the redox process of dye molecules and macromolecular segments when exposed to light, thereby improving the sun resistance and strength retention of fabrics.

[0003] At present, the widely used organic and inorganic ultraviolet absorbers can effectively improve the anti-ultraviolet performance of fabrics in the short term, but they still have the disadvantages of low affinity with polymer substrates and poor dispersion stability, which are not conducive to long-term ultraviolet exposure of outdoor fabrics. Patent CN115182173A discloses a method for improving the sun resistance of fabrics, in which a self-adhesive anti-ultraviolet microcapsule is prepared by using materials such as azobisisobutyl cyanide, ethyl acrylate, styrene and organic ultraviolet absorbers, and then cured on the surface of the fabric to form a film, giving the fabric a certain anti-ultraviolet performance. In addition, CN113430836A discloses a simple finishing process for improving the anti-ultraviolet performance of polyester, in which inorganic ultraviolet absorbers are arranged on the surface of polyester fibers by secondary spray curing. In summary, although various types of existing organic / inorganic ultraviolet absorbing materials have been developed to improve the anti-ultraviolet performance of fabrics, complex modification methods are still needed during the application process to solve the problems of low affinity between ultraviolet absorbers and polymer substrates and poor dispersion stability. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides a bio-based anti-ultraviolet finishing agent and a preparation method thereof. The overall agent of the present invention can solve the problems of low affinity between the ultraviolet absorber and the polymer substrate and poor dispersion stability, and utilizes its excellent spontaneous drying film-forming performance to effectively protect the dye chromophores and polymer segments on the fabric through a simple coating finishing process, thereby significantly improving the sun resistance and strong retention performance of the fabric under outdoor high-intensity ultraviolet radiation.

[0005] The technical solution of the present invention is as follows:

[0006] The first object of the present invention is to provide a method for preparing a bio-based anti-ultraviolet finishing agent, comprising the following steps:

[0007] (1) adding an ultraviolet absorber and / or an ultraviolet shielding agent into a solvent and performing ultrasonic dispersion to obtain a dispersion;

[0008] (2) adding cellulose nanofibers to the dispersion and stirring at 30-70° C. for 2-6 hours to obtain the bio-based anti-ultraviolet finishing agent;

[0009] The aspect ratio of the cellulose nanofibers is 100-10000.

[0010] In one embodiment of the present invention, in step (1), the ultraviolet absorber is one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(2,4-di-tert-butylbenzene) phosphite, 2,2'-methylenebis(4-tert-octyl-6-benzotriazolephenol), 2-(2'-hydroxy-3'-cumyl-5'-tert-octylphenyl)benzotriazole, and 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol.

[0011] In one embodiment of the present invention, in step (1), the ultraviolet shielding agent is one or more of zinc oxide, titanium dioxide, strontium titanate, silicon dioxide, and aluminum oxide.

[0012] In one embodiment of the present invention, in step (1), the solvent is one of deionized water, ethanol, dichloromethane, ethyl acetate, methanol, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and acetone.

[0013] In one embodiment of the present invention, in step (1), the mass volume ratio of the ultraviolet absorber and / or ultraviolet shielding agent to the solvent is 1-100 g / L.

[0014] In one embodiment of the present invention, the power of ultrasonic dispersion is 0.5-5KW, and the time is 2-20min.

[0015] In one embodiment of the present invention, in step (2), the length of the cellulose nanofibers is 1-1000 μm and the diameter is 5-100 nm.

[0016] In one embodiment of the present invention, in step (2), the terminal functional groups of the cellulose nanofibers are one of carboxyl, amino, phosphate, acrylate, methyl methacrylate, butyl acrylate, maleic anhydride, acryloyl chloride, alkyl ketene dimer, alkenyl succinic anhydride, and siloxane; and the content of the terminal functional groups is 0.2-2wt%.

[0017] In one embodiment of the present invention, in step (2), the molar ratio of cellulose nanofibers to ultraviolet absorbers and / or ultraviolet shielding agents is 0.1-10:1.

[0018] In one embodiment of the present invention, in step (2), the stirring rate is 1000-10000 rpm.

[0019] The second object of the present invention is to provide a bio-based anti-ultraviolet finishing agent prepared by the above preparation method.

[0020] The solid content of the bio-based anti-ultraviolet finishing agent is 1-10wt%.

[0021] The third object of the present invention is to provide a use of the above bio-based anti-ultraviolet finishing agent for finishing colored fabrics.

[0022] In one embodiment of the present invention, the finishing method is one of dipping, coating, spraying and rolling.

[0023] In one embodiment of the present invention, the dye used for dyeing colored fabrics is one of acid dyes, cationic dyes, direct dyes, disperse dyes, azo dyes, reactive dyes, and vat dyes.

[0024] In one embodiment of the present invention, the colored fabric is made of a blend of one or more fibers of cotton, linen, wool, silk, viscose, nylon, polyester, acrylic, spandex, nylon, polypropylene, and chloroprene.

[0025] In one embodiment of the present invention, the weight gain of the colored fabric after finishing is 1-10%.

[0026] The beneficial technical effects of the present invention are:

[0027] The present invention encapsulates the ultraviolet absorber or shielding agent through cellulose nanofibers with high aspect ratio and rich hydrogen bonding force, and utilizes its excellent spontaneous drying film-forming performance to effectively protect the dye chromophore groups and polymer segments on the fabric through a simple finishing process, thereby significantly improving the sun resistance and strong retention performance of the fabric under outdoor high-intensity ultraviolet radiation.

[0028] The present invention does not require additional chemical cross-linking, but utilizes the entanglement effect of cellulose nanofibers to in-situ encapsulate the ultraviolet absorber, does not require the addition of additional polymer film-forming materials, and utilizes the hydrogen bonding between cellulose fibers and substrates to spontaneously dry and form a film. DETAILED DESCRIPTION

[0029] The test method is analyzed as follows:

[0030] According to "GB / T 8427-2019 Textiles - Color fastness to artificial light: Xenon arc shading", the dyed fabrics were tested for their sunlight resistance. According to "GB / T 8424.3-2001 Textiles - Color fastness - Color difference calculation" the color difference ΔE of the dyed fabrics before and after exposure was calculated. CMC According to GB / T 3923.1-2013 Tensile Properties of Textile Fabrics, the breaking strength of dyed fabrics before and after exposure was measured.

[0031] Example 1

[0032] A method for preparing a bio-based anti-ultraviolet finishing agent comprises the following steps:

[0033] Disperse 2 g of zinc oxide in 180 ml of deionized water and ultrasonically disperse for 60 min to form a uniformly dispersed zinc oxide dispersion;

[0034] Subsequently, 0.5 g of carboxylated cellulose nanofibers (carboxyl content 0.5 wt%) with an aspect ratio of 500 was added to the dispersion, and the reaction was stirred at 60°C and 5000 rpm / min for 4 hours; the product was then concentrated by low-speed centrifugation and washed several times with deionized water to obtain a nano core-shell composite cellulose-based anti-ultraviolet finishing agent with a solid content of 2 wt%.

[0035] The red, yellow and blue dyed polyester fabrics were immersed in the nano core-shell composite cellulose-based anti-ultraviolet finishing agent respectively, and then immersed and pressed twice after 10 minutes, and dried at room temperature for 12 hours to obtain the coating-modified dyed polyester fabrics.

[0036] According to GB / T 8427-2019, GB / T 8424.3-2001 and GB / T 3923.1-2013, the color and breaking strength of the coated modified dyed polyester fabrics were tested after exposure for 100 hours (Table 1). The three different colored dyed fabrics all showed excellent sunlight resistance, with the surface color depth K / S and color difference ΔE CMC The variation is extremely low and the breaking strength remains almost unchanged.

[0037] Example 2

[0038] A method for preparing a bio-based anti-ultraviolet finishing agent comprises the following steps:

[0039] Disperse 2 g of zinc oxide in 180 ml of deionized water and ultrasonically disperse for 60 min to form a uniformly dispersed zinc oxide dispersion;

[0040] Subsequently, 0.5 g of carboxylated cellulose nanofibers (carboxyl content 0.5 wt%) with an aspect ratio of 500 was added to the dispersion, and the reaction was stirred at 60°C and 5000 rpm / min for 4 hours; the product was then concentrated by low-speed centrifugation and washed with deionized water for multiple times to obtain a nano core-shell composite cellulose-based anti-ultraviolet finishing agent with a solid content of 4 wt%.

[0041] The red, yellow and blue dyed polyester fabrics were immersed in the nano core-shell composite cellulose-based anti-ultraviolet finishing agent respectively, and then immersed and pressed twice after 10 minutes, and dried at room temperature for 12 hours to obtain the coating-modified dyed polyester fabrics.

[0042] According to GB / T 8427-2019, GB / T 8424.3-2001 and GB / T 3923.1-2013, the color and breaking strength of the coated modified dyed polyester fabrics were tested after exposure for 100 hours (Table 1). The three different colored dyed fabrics all showed excellent sunlight resistance, with the surface color depth K / S and color difference ΔE CMC The variation is extremely low and the breaking strength remains almost unchanged.

[0043] Example 3

[0044] A method for preparing a bio-based anti-ultraviolet finishing agent comprises the following steps:

[0045] Disperse 2 g of zinc oxide in 180 ml of deionized water and ultrasonically disperse for 60 min to form a uniformly dispersed zinc oxide dispersion;

[0046] Subsequently, 1 g of carboxylated cellulose nanofibers (carboxyl content 0.5 wt%) with an aspect ratio of 500 was added to the dispersion, and the reaction was stirred at 60°C and 5000 rpm / min for 4 hours; the product was then concentrated by low-speed centrifugation and washed with deionized water for multiple times to obtain a nano core-shell composite cellulose-based anti-ultraviolet finishing agent with a solid content of 2 wt%.

[0047] The red, yellow and blue dyed polyester fabrics were immersed in the nano core-shell composite cellulose-based anti-ultraviolet finishing agent respectively, and then immersed and pressed twice after 10 minutes, and dried at room temperature for 12 hours to obtain the coating-modified dyed polyester fabrics.

[0048] According to GB / T 8427-2019, GB / T 8424.3-2001 and GB / T 3923.1-2013, the color and breaking strength of the coated modified dyed polyester fabrics were tested after exposure for 100 hours (Table 1). The three different colored dyed fabrics all showed excellent sunlight resistance, with the surface color depth K / S and color difference ΔE CMC The variation is extremely low and the breaking strength remains almost unchanged.

[0049] Example 4

[0050] A method for preparing a bio-based anti-ultraviolet finishing agent comprises the following steps:

[0051] Disperse 1 g of zinc oxide in 180 ml of deionized water and ultrasonically disperse for 60 min to form a uniformly dispersed zinc oxide dispersion;

[0052] Subsequently, 0.5 g of carboxylated cellulose nanofibers (carboxyl content 0.5 wt%) with an aspect ratio of 500 was added to the dispersion, and the reaction was stirred at 60°C and 5000 rpm / min for 4 hours; the product was then concentrated by low-speed centrifugation and washed several times with deionized water to obtain a nano core-shell composite cellulose-based anti-ultraviolet finishing agent with a solid content of 2 wt%.

[0053] The red, yellow and blue dyed polyester fabrics were immersed in the nano core-shell composite cellulose-based anti-ultraviolet finishing agent respectively, and then immersed and pressed twice after 10 minutes, and dried at room temperature for 12 hours to obtain the coating-modified dyed polyester fabrics.

[0054] According to GB / T 8427-2019, GB / T 8424.3-2001 and GB / T 3923.1-2013, the color and breaking strength of the coated modified dyed polyester fabrics were tested after exposure for 100 hours (Table 1). The three different colored dyed fabrics all showed excellent sunlight resistance, with the surface color depth K / S and color difference ΔE CMC The variation is extremely low and the breaking strength remains almost unchanged.

[0055] Example 5

[0056] A method for preparing a bio-based anti-ultraviolet finishing agent comprises the following steps:

[0057] Disperse 2 g of zinc oxide in 180 ml of deionized water and ultrasonically disperse for 60 min to form a uniformly dispersed zinc oxide dispersion;

[0058] Subsequently, 1 g of carboxylated cellulose nanofibers (carboxyl content 0.5 wt%) with an aspect ratio of 500 was added to the dispersion and reacted at 60°C and 5000 rpm / min for 4 h; the product was then concentrated by low-speed centrifugation and washed multiple times with deionized water to obtain a nano core-shell composite cellulose-based anti-ultraviolet finishing agent with a solid content of 4 wt%.

[0059] The red, yellow and blue dyed polyester fabrics were immersed in the nano core-shell composite cellulose-based anti-ultraviolet finishing agent respectively, and then immersed and pressed twice after 10 minutes, and dried at room temperature for 12 hours to obtain the coating-modified dyed polyester fabrics.

[0060] According to GB / T 8427-2019, GB / T 8424.3-2001 and GB / T 3923.1-2013, the color and breaking strength of the coated modified dyed polyester fabrics were tested after exposure for 100 hours (Table 1). The three different colored dyed fabrics all showed excellent sunlight resistance, with the surface color depth K / S and color difference ΔE CMC The variation is extremely low and the breaking strength remains almost unchanged.

[0061] Example 6

[0062] A method for preparing a bio-based anti-ultraviolet finishing agent comprises the following steps:

[0063] Dispersing 2 g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate in 180 ml of deionized water and ultrasonically dispersing for 60 min to form a uniformly dispersed pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate dispersion;

[0064] Subsequently, 1 g of carboxylated cellulose nanofibers (carboxyl content 0.5 wt%) with an aspect ratio of 500 was added to the dispersion, and the reaction was stirred at 60°C and 5000 rpm / min for 4 hours; the product was then concentrated by low-speed centrifugation and washed with deionized water for multiple times to obtain a nano core-shell composite cellulose-based anti-ultraviolet finishing agent with a solid content of 4 wt%.

[0065] The red, yellow and blue dyed polyester fabrics were immersed in the nano core-shell composite cellulose-based anti-ultraviolet finishing agent respectively, and then immersed and pressed twice after 10 minutes, and dried at room temperature for 12 hours to obtain the coating-modified dyed polyester fabrics.

[0066] According to GB / T 8427-2019, GB / T 8424.3-2001 and GB / T 3923.1-2013, the color and breaking strength of the coated modified dyed polyester fabrics were tested after exposure for 100 hours (Table 1). The three different colored dyed fabrics all showed excellent sunlight resistance, with the surface color depth K / S and color difference ΔE CMC The variation is extremely low and the breaking strength remains almost unchanged.

[0067] Example 7

[0068] A method for preparing a bio-based anti-ultraviolet finishing agent comprises the following steps:

[0069] Dispersing 1 g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and 1 g of zinc oxide in 180 ml of deionized water and ultrasonically dispersing for 60 min to form a uniformly dispersed pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate / zinc oxide dispersion;

[0070] Subsequently, 1 g of carboxylated cellulose nanofibers (carboxyl content 0.5 wt%) with an aspect ratio of 500 was added to the dispersion, and the reaction was stirred at 60°C and 5000 rpm / min for 4 hours; the product was then concentrated by low-speed centrifugation and washed with deionized water for multiple times to obtain a nano core-shell composite cellulose-based anti-ultraviolet finishing agent with a solid content of 4 wt%.

[0071] The red, yellow and blue dyed polyester fabrics were immersed in the nano core-shell composite cellulose-based anti-ultraviolet finishing agent respectively, and then immersed and pressed twice after 10 minutes, and dried at room temperature for 12 hours to obtain the coating-modified dyed polyester fabrics.

[0072] According to GB / T 8427-2019, GB / T 8424.3-2001 and GB / T 3923.1-2013, the color and breaking strength of the coated modified dyed polyester fabrics were tested after exposure for 100 hours (Table 1). The three different colored dyed fabrics all showed excellent sunlight resistance, with the surface color depth K / S and color difference ΔE CMC The variation is extremely low and the breaking strength remains almost unchanged.

[0073] Comparative Example 1

[0074] A method for preparing an anti-ultraviolet finishing agent comprises the following steps:

[0075] Disperse 2 g of zinc oxide in 180 ml of deionized water and ultrasonically disperse for 60 min to form a uniformly dispersed zinc oxide dispersion;

[0076] The mixture was stirred at 60° C. and 5000 rpm / min for 4 h; the product was then concentrated by low-speed centrifugation, washed with deionized water for multiple times, and then dispersed, wherein the solid content of the dispersion was 2 wt %.

[0077] The red, yellow and blue dyed polyester fabrics were immersed in the above dispersion respectively, and then immersed and pressed twice after 10 minutes, and dried at room temperature for 12 hours to obtain the coating-modified dyed polyester fabrics.

[0078] According to GB / T 8427-2019, GB / T 8424.3-2001 and GB / T 3923.1-2013, the color and breaking strength of the coated modified dyed polyester fabric were tested after exposure for 100 hours (Table 1). The sun resistance of the three different colored dyed fabrics was poor, among which the surface color depth K / S and color difference ΔE CMC The change is large and the breaking strength decreases significantly.

[0079] Comparative Example 2

[0080] A method for preparing an anti-ultraviolet finishing agent comprises the following steps:

[0081] 1 g of carboxylated cellulose nanofibers (carboxyl content 0.5 wt%) with an aspect ratio of 500 was added to 180 ml of deionized water and stirred at 60°C and 5000 rpm / min for 4 h; the product was then concentrated by low-speed centrifugation and dispersed after multiple washings with deionized water, wherein the solid content of the dispersion was 2 wt%.

[0082] The red, yellow and blue dyed polyester fabrics were immersed in the above dispersion respectively, and then immersed and pressed twice after 10 minutes, and dried at room temperature for 12 hours to obtain the coating-modified dyed polyester fabrics.

[0083] According to GB / T 8427-2019, GB / T 8424.3-2001 and GB / T 3923.1-2013, the color and breaking strength of the coated modified dyed polyester fabric were tested after exposure for 100 hours (Table 1). The sun resistance of the three different colored dyed fabrics was poor, among which the surface color depth K / S and color difference ΔE CMC The change is large and the breaking strength decreases significantly.

[0084] Table 1 Sunlight resistance of red, yellow and blue polyester dyed fabrics

[0085]

[0086]

[0087] Although the present invention has been disclosed as above in terms of preferred embodiments, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be defined by the claims.

Claims

1. A method for preparing a bio-based anti-ultraviolet finishing agent, characterized in that: The steps include: (1) adding an ultraviolet absorber and / or an ultraviolet shielding agent into a solvent and performing ultrasonic dispersion to obtain a dispersion; (2) adding cellulose nanofibers to the dispersion and stirring at 30-70° C. for 2-6 hours to obtain the bio-based anti-ultraviolet finishing agent; The aspect ratio of the cellulose nanofiber is 100-10000.

2. The preparation method according to claim 1, characterized in that: In step (1), the ultraviolet absorber is one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(2,4-di-tert-butylbenzene) phosphite, 2,2'-methylenebis(4-tert-octyl-6-benzotriazolephenol), 2-(2'-hydroxy-3'-cumyl-5'-tert-octylphenyl)benzotriazole, and 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol.

3. The preparation method according to claim 1, characterized in that: In step (1), the ultraviolet shielding agent is one or more of zinc oxide, titanium dioxide, strontium titanate, silicon dioxide, and aluminum oxide.

4. The preparation method according to claim 1, characterized in that: In step (1), the solvent is one of deionized water, ethanol, dichloromethane, ethyl acetate, methanol, N,N-dimethylformamide, N,N-dimethylacetamide, and acetone.

5. The preparation method according to claim 1, characterized in that: In step (1), the mass volume ratio of the ultraviolet absorber and / or ultraviolet shielding agent to the solvent is 1-100 g / L.

6. The preparation method according to claim 1, characterized in that: In step (2), the length of the cellulose nanofibers is 1-1000 μm and the diameter is 5-100 nm.

7. The preparation method according to claim 1, characterized in that: In step (2), the terminal functional groups of the cellulose nanofibers are one of carboxyl, amino, phosphate, acrylate, methyl methacrylate, butyl acrylate, maleic anhydride, acryloyl chloride, alkyl ketene dimer, alkenyl succinic anhydride, and siloxane; and the terminal functional group content is 0.2-2wt%.

8. The preparation method according to claim 1, characterized in that: In step (2), the molar ratio of cellulose nanofibers to ultraviolet absorber and / or ultraviolet shielding agent is 0.1-10:

1.

9. A bio-based anti-ultraviolet finishing agent prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the bio-based anti-ultraviolet finishing agent according to claim 9, characterized in that: For finishing colored fabrics.

Citation Information

Patent Citations

  • Light and thin anti-ultraviolet sun-resistant flame-retardant fabric

    CN115182173A

Cited By

  • Preparation method and application of anti-ultraviolet finishing liquid based on composite nano material

    CN121161593A